2001
DOI: 10.3323/jcorr1991.50.115
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of Coated Steel Panels on Automobiles and its Corrosion Mechanism

Abstract: The effect of galvanized corrosion steel sheets and zinc-rich primer coated steel sheets on the perforation corrosion of actual automobiles and the relevant corrosion mechanism was studied. Perforation occurred in 6-7 years for zinc-rich primer coated steel panels inside of door hems and after more than 14 years for galvanized steel sheets with 120g/m2 zinc coating mass in the lapped side-sill. Perforation corrosion of galvanized steel panels can be divided into 4 corrosion processes on the basis of measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…An investigations of corroded vehicles used in snowy areas showed that perforation corrosion of automotive parts tends to be prevented as the coating thickness increases. 26,27,29,30) Although sales of automobiles in tropical regions in Asia have increased in the last 10 years, there are still few reports on corrosion of vehicles in those environments. Therefore, this paper reports the corrosion of vehicles used in two different regions, snowy areas in Europe (Austria, Denmark and Sweden) and a tropical area in Asia (Thailand).…”
Section: Analysis Of Corroded Vehiclesmentioning
confidence: 99%
See 3 more Smart Citations
“…An investigations of corroded vehicles used in snowy areas showed that perforation corrosion of automotive parts tends to be prevented as the coating thickness increases. 26,27,29,30) Although sales of automobiles in tropical regions in Asia have increased in the last 10 years, there are still few reports on corrosion of vehicles in those environments. Therefore, this paper reports the corrosion of vehicles used in two different regions, snowy areas in Europe (Austria, Denmark and Sweden) and a tropical area in Asia (Thailand).…”
Section: Analysis Of Corroded Vehiclesmentioning
confidence: 99%
“…1. 27) The time to perforation corrosion is divided into the protection period by the zinc coating and the corrosion period of the steel substrate. The protection by the zinc coating is attributed to the good corrosion resistance of the zinc itself under the atmosphere (τ 1 ), sacrificial corrosion of zinc (τ 2 ) and protection by the deposited zinc corrosion products (τ 3 ).…”
Section: Perforation Corrosion Behavior Of Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of "perforation corrosion" has been studied extensively based on an analysis of actual vehicles, 2) and the effects of anti-corrosion steel sheets under various corrosion environments have been clarified. 3) Regarding "cosmetic corrosion", in other words, "under-film corrosion", it is generally known that the anodic and cathodic sites are localized and show the morphology of macro corrosion.…”
Section: Introductionmentioning
confidence: 99%